1998
DOI: 10.1590/s0100-879x1998000600004
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific blockade of vascular free radical signals by methylated arginine analogues

Abstract: Methylated arginine analogues are often used as probes of the effect of nitric oxide; however, their specificity is unclear and seems to be frequently overestimated. This study analyzed the effects of N Gmethyl-L-arginine (L-NMMA) on the endothelium-dependent release of vascular superoxide radicals triggered by increased flow. Plasma ascorbyl radical signals measured by direct electron paramagnetic resonance spectroscopy in 25 rabbits increased by 3.8 ± 0.7 nmol/l vs baseline (28.7 ± 1.4 nmol/l, P<0.001) in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…It was reported that the vasoconstrictor effect of L-NMMA involved superoxide production (50, 60) via activation of cyclooxygenase with the resultant increased production of superoxide inactivating endothelium-derived relaxing factor (NO) (50). On the other hand, L-NMMA inhibited endotheliumdependent release of superoxide induced by increased blood flow (44). Any nonspecific effect of L-NMMA remains to be further established.…”
Section: Discussionmentioning
confidence: 91%
“…It was reported that the vasoconstrictor effect of L-NMMA involved superoxide production (50, 60) via activation of cyclooxygenase with the resultant increased production of superoxide inactivating endothelium-derived relaxing factor (NO) (50). On the other hand, L-NMMA inhibited endotheliumdependent release of superoxide induced by increased blood flow (44). Any nonspecific effect of L-NMMA remains to be further established.…”
Section: Discussionmentioning
confidence: 91%
“…Several mechanisms may be responsible for the L ‐NMMA–induced venodilation: First, activation of α 1 ‐adrenergic receptors stimulates the production of reactive oxygen species, 36 , 37 which contribute to vasoconstriction. Because L ‐NMMA is a scavenger of reactive oxygen species, 38 , 39 it could induce a reversal of venoconstriction. Second, the NO synthase inhibitors L ‐NMMA and N ω ‐nitro‐ L ‐arginine methyl ester ( L ‐NAME) are able to directly block the mammalian nicotinic acetylcholine receptor channels, 13 suggesting blunted in vivo activity of the sympathetic nerve terminals.…”
Section: Discussionmentioning
confidence: 99%